2011
DOI: 10.5194/acp-11-8343-2011
|View full text |Cite
|
Sign up to set email alerts
|

Hygroscopic properties of the ambient aerosol in southern Sweden – a two year study

Abstract: Abstract. The hygroscopic growth of the atmospheric aerosol is a critical parameter for quantifying the anthropogenic radiative forcing. Until now, there has been a lack of long term measurements due to limitations in instrumental techniques. In this work, for the first time the seasonal variation of the hygroscopic properties of a continental background aerosol has been described, based on more than two years of continuous measurements. In addition to this, the diurnal variation of the hygroscopic growth has … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
60
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 39 publications
9
60
1
Order By: Relevance
“…The median number fraction of hydrophilic mode for 50 nm particles was 0.6, which was smaller than that of larger particles. Fors et al (2011) also reported that smaller particles had a higher fraction of less hygroscopic particles in southern Sweden. Larger particles (here, above 150 nm) constituting a larger fraction of the hydrophilic mode can be explained as such: in the urban area, traffic emissions are major sources for particles below 100 nm.…”
Section: Overview Of Particle Hygroscopic Growth and The Mixing Statementioning
confidence: 98%
“…The median number fraction of hydrophilic mode for 50 nm particles was 0.6, which was smaller than that of larger particles. Fors et al (2011) also reported that smaller particles had a higher fraction of less hygroscopic particles in southern Sweden. Larger particles (here, above 150 nm) constituting a larger fraction of the hydrophilic mode can be explained as such: in the urban area, traffic emissions are major sources for particles below 100 nm.…”
Section: Overview Of Particle Hygroscopic Growth and The Mixing Statementioning
confidence: 98%
“…Laboratory and field studies of secondary organic aerosol (SOA) species have found κ values around ∼0.1 (Prenni et al, 2007;Engelhart et al, 2008;Engelhart et al, 2011;Wex et al, 2009;Pierce et al, 2012) although individual species, when separated by polarity, show a larger range (Suda et al, 2012). Studies have shown that κ of more oxidized secondary organic species can be as high as 0.22 (Chang et al, 2010), although Frosch et al (2011) found no relationship between κ and O / C ratio for α-pinene SOA aged in a smog chamber. Black carbon and dust are typically measured or assumed to have κ values of ∼0-0.05 (Koehler et al, 2009;Yamashita et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…In addition to the DMPS data, CCN number concentrations at fixed supersaturations were measured in Hyytiälä and Vavihill using a cloud condensation nuclei counter (CCNC) over limited time periods. For detailed descriptions of the measurements systems at each location, we refer to Hari and Kulmala (2005), Kristensson et al (2008), Laakso et al (2008), , Fors et al (2011) and Sihto et al (2011).…”
Section: Examples Of Recent Long-term Observationsmentioning
confidence: 99%